Study on Tooth Profile Synthesis and Nonlinear Mechanical Property of Dual Shock Wave Sleeve Movable Tooth Transmission - Liu Jun; An Zijun (Jixie chuandong)
According to the structure and transmission principle of the dual shock wave sleeve movable tooth transmission，the equation of central tooth profile has been derived. On the premise that the working tooth profile of the center wheel does not interfere，the relationship between structural parameters is established. Considering the nonlinear relationship between the load and deformation and the influence of the hollow degree of the movable tooth on the deformation，the nonlinear mechanical model of meshing pair is established to analysis the nonlinear meshing force，changing law and influencing factors of each meshing pair. A non-Hertz contact analysis model is established for the structural characteristics of finite long line contact meshing of each meshing pair of the sleeve，and the effective contact area and contact fatigue stress of each mesh pair are solved by numerical method. The contact fatigue strength of each mesh pair and the bending fatigue strength of the pin are analyzed. The results show that the relationship of structural parameters and the influence factors of meshing force provide reference for the design of double shock sleeve movable tooth transmission，by using the non-Hertz contact model and the nonlinear mechanical model， which take into account the hollowness， the error caused by simplification based on linear elasticity and hertz theory can be reduced， and the strength calculation is more in line with practical situation.